STOCHASTIC DYNAMICS OF THE ACCOMMODATION APPARATUS OF EYES OF THE OPERATOR OF THE PERSONAL COMPUTER (PC) - Лютый, Александр Павлович; Михайлова, Татьяна Ивановна; Труфанов, Иван Дмитриевич; Шмирко, Вера Ивановна; Дудник, Георгий Иванович; Чумаков, Кирилл Игоревич (Eastern-European Journal of Enterprise Technologies, 2010)
The computer stochastic analysis of semiology of complaints to health of the operator of the PC is carried out. Influence visual colour-impulse stimulations on recovery of visual function of serviceability of the operator of the PC is researched.